2014
DOI: 10.1084/jem.20132349
|View full text |Cite
|
Sign up to set email alerts
|

CARD9 mediates Dectin-1–induced ERK activation by linking Ras-GRF1 to H-Ras for antifungal immunity

Abstract: CARD9 is dispensable for NF-κB activation induced by Dectin-1 ligands in mice. However, Dectin-1–induced H-Ras activation is mediated by a complex with CARD9, which leads to ERK activation for host innate immune responses to Candida albicans infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 64 publications
(107 reference statements)
6
111
0
Order By: Relevance
“…6G). Our data are consistent with previous observations that ERK signaling is required for the production of TNF␣ and IL-6 downstream of Dectin-1 (30,36). p38 signaling in macrophages and dendritic cells has also been shown to contribute to pro-inflammatory cytokine production (37,38).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…6G). Our data are consistent with previous observations that ERK signaling is required for the production of TNF␣ and IL-6 downstream of Dectin-1 (30,36). p38 signaling in macrophages and dendritic cells has also been shown to contribute to pro-inflammatory cytokine production (37,38).…”
Section: Discussionsupporting
confidence: 93%
“…PLC␥2 products also activate PKC␦, which then phosphorylates the adaptor protein CARD9, resulting in activation of the NF-B pathway (15). A recent study showed that CARD9 also plays a critical role in ERK activation by bringing together Ras and RasGRF1, resulting in the activation of Ras and ERK further downstream (30). However, the existence of CARD9-independent pathways cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dectin-1 signaling regulates ERK (also known as MAP kinase) activity via H-RAS and RAS guanine nucleotide-releasing factor 1 (RASGRF1) (39). This pathway regulates macrophage IL-6, IL-1β, and TNF, but not IL-12 responses, and is protective during systemic candidiasis (39).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Dectin-1 can collaborate with TLRs to orchestrate antifungal immunity. 5 During C. albicans bloodstream infection, which may present as sepsis and septic shock, innate responses govern the early response. Neutrophils are considered principal effector cells conferring protection.…”
mentioning
confidence: 99%